Wage Flexibility or Wage Coordination? Economic Policy Implications of the Wage-led Demand Regime in the Euro Area - Engelbert Stockhammer (Intervention. European Journal of Economics and Economic Policies, 2008)
First paragraph: Functional income distribution has shifted dramatically in the past 25 years. The wage share in the Euro area has fallen by ten percentage points since 1981.
Keywords: 330